2007
DOI: 10.1051/0004-6361:20066746
|View full text |Cite
|
Sign up to set email alerts
|

Planets ofβ Pictoris revisited

Abstract: Observations have revealed a large variety of structures (global asymmetries, warps, belts, rings) and dynamical phenomena ("fallingevaporating bodies" or FEBs, the "β Pic dust stream") in the disk of β Pictoris, most of which may indicate the presence of one or more planets orbiting the star. Because planets of β Pic have not been detected by observations yet, we use dynamical simulations to find "numerical evidence" for a planetary system. We show that one planet at 12 AU with a mass of 2 to 5 M J and an ecc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 23 publications
4
45
0
Order By: Relevance
“…The other two were around the A-type stars Fomalhaut (Kalas et al 2008), which is the first planet candidate discovered in the optical regime using the Hubble Space Telescope (HST), and β Pic (Lagrange et al 2009(Lagrange et al , 2010, a planet within the large edge-on disk at only about twice the separation of Jupiter from the Sun. This had previously been predicted by Freistetter et al (2007), for instance, from the structural gaps in the disk.…”
Section: Introductionsupporting
confidence: 57%
“…The other two were around the A-type stars Fomalhaut (Kalas et al 2008), which is the first planet candidate discovered in the optical regime using the Hubble Space Telescope (HST), and β Pic (Lagrange et al 2009(Lagrange et al , 2010, a planet within the large edge-on disk at only about twice the separation of Jupiter from the Sun. This had previously been predicted by Freistetter et al (2007), for instance, from the structural gaps in the disk.…”
Section: Introductionsupporting
confidence: 57%
“…The existence of a giant planet orbiting β Pic has been proposed by various studies during the past few decades (e.g. Freistetter et al 2007). The main indirect indicators are (i) the inner warped component of the β Pic circumstellar disk, together with additional asymmetries observed in the outer part (Mouillet et al 1997;Kalas & Jewitt 1995); (ii) the photometric transit-like event observed in 1981 (Lecavelier des Etangs et al 1997); and (iii) the cometary activity observed in the absorption spectrum of β Pic (Ferlet et al 1987;Lagrange et al 1996;VidalMadjar et al 1998;Petterson & Tobin 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The star hosts an ∼1000-AU-wide gas-rich debris disk (Smith & Terrile 1984) presented nearly edge-on. Asymmetries in the disk and variability in high-resolution spectra indicative of dynamic comets (Kiefer et al 2014) suggested the presence of one or more planets long before the discovery of β Pic b itself (Lagrange-Henri et al 1988;Beust et al 1990;Roques et al 1993;Levison et al 1994;Mouillet et al 1997;Freistetter et al 2007;Beust & Valiron 2007). Finally, the giant exoplanet β Pic b was imaged (Lagrange et al 2009) and confirmed (Lagrange et al 2010) using adaptive optics (AO) at VLT/NaCo.…”
Section: Introductionmentioning
confidence: 97%